Relationships between human resource development and extension agents' work performance among cocoa growers in Malaysia - Oluwatoyin, Olagunju; Hassan, Salim; Abd Samad, Mohd Yusoff; Suandi, Turiman; Kasin, Ramle (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Currently one of the challenges facing extension agents is their inability to develop the potential of the farmers towards crop production and this can be attributed to low performance in human resource development initiatives among the farmers. This study aimed at determining how human resource development is related to work performance of extension agents among cocoa growers in Malaysia. The study used stratified sampling technique to select 668 productive cocoa growers who are exposed to extension activities facilitated by the extension agents’ of Malaysian Cocoa Board (MCB) in the three (3) regions of Malaysia. The data were analyzed using descriptive statistics, Pearson correlation and multiple linear regression. Demographic profile indicated that majority of the farmers involved in cocoa production are ageing which may serves as constraints to yield improvement. Also, majority of the farmers had only completed primary education and usually taking cocoa as a part time job. Significant and positive correlation (P<0.01) existed between each variables and extension agents’ work performance. Multiple regression analysis results showed that leadership skill, decision making support skill, and social skill are significant (p<0.05) determinants. The Adj.R2 value of 0.562 implies that three predictors explain about 56.2% of the variation in extension agents’ work performance. The highest contribution is attributed by decision making support skill (β=0.321). Findings revealed that extension agents needs to be knowledgeable and skilful in human resource development through regular training programmes so as to be able to establish effective working relationships with co-workers, colleagues, supervisors, volunteers, farmers and key community leaders which is very important in improving their performance as well as enhance farmers sustainable cocoa production.